Implementasi Metode Multi Attribute Utility Theory Untuk Sistem Pendukung Keputusan Pada Pembelian Motor Bekas - Ridho Bestariyanto, Ginda Ali; Dasuki, Moh.; Bakti, Budi Satria` (UNIB Press, 2025)
Motorbikes are one of the most widely used means of transportation to support daily activities. Not all individuals are able to buy the latest motorbikes. Some choose to buy used motorbikes. In order to acquire a top-notch pre-owned motorbike, one must possess a keen eye and the ability to select a used motorcycle meticulously, following one's specific requirements. Sometimes, people require the service of an inspector to thoroughly assess the condition of a pre-owned motorbike, ensuring it meets all the required criteria. This research employs the Multi-Attribute Utility Theory (MAUT) technique to assist as a decision support system for prospective buyers of pre-owned motorcycles. Nine criteria are considered as attributes in this approach. The primary objective of this decision support system is to greatly minimize the likelihood of human error when inspecting pre-owned motorcycles. It will ensure that potential buyers are guaranteed the highest quality used motorbikes. The highest recommended used motorcycles were determined through calculations using the Multi Attribute Utility Theory (MAUT) method, based on a selection of several alternatives chosen by the buyer.